Immune responses to Crimean-Congo haemorrhagic fever virus and molecular characterization of viral isolates - Goedhals, Dominique (University of the Free State, 2014)
Crimean-Congo haemorrhagic fever virus (CCHFV) is a tick-borne virus belonging to the family Bunyaviridae, genus Nairovirus. The distribution of the virus correlates with that of the principal vector, ticks belonging to the genus Hyalomma. This includes areas in Africa, Asia, Eastern Europe and the Middle East, with recent emergence in Turkey, Greece and India. CCHFV is associated with haemorrhagic fever in humans, with a case fatality rate of up to 30%. Current patient management relies on supportive therapy and administration of ribavirin, but the efficacy of this antiviral drug is controversial. Although an inactivated vaccine has been used in Eastern Europe and the former Soviet Union, it has not been accepted for widespread use. An understanding of immune correlates is therefore needed to guide further development of therapeutic and preventative interventions. This study aimed to investigate immune responses in survivors of CCHF in South Africa, focusing on the presence of detectable memory T lymphocyte responses and the identification of epitopic regions within the nucleoprotein and glycoproteins. In order to ensure applicability of identified epitopes to geographically distinct isolates, viral sequence diversity was also investigated by means of next generation sequencing and phylogenetic studies. A synthetic overlapping peptide library was used to screen for interferon gamma production by peripheral blood mononuclear cells from survivors of CCHFV infection in ELISPOT assays. Ten potential epitopic regions were identified, the majority of which were located on the nucleoprotein with only two regions identified on the glycoprotein GC in a single patient. Long-lived memory CD8+ T cell responses were detected in survivors of CCHF up to 13 years after infection. These findings indicate the presence of effective long term cellular immune responses which could be modulated through vaccination and gives an indication of epitopic regions that should be considered in candidate vaccines and testing vaccine immunogenicity. The presence of detectable memory responses in the absence of reexposure or chronic infection will allow future studies to fully characterize T cell responses in survivors. With an expanding area of CCHFV endemicity, safe, sensitive and specific serological assays are required for diagnostic and serosurveillance purposes. As the biosafety level 4 facilities required to culture the virus are lacking in many endemic areas, alternative means of producing reagents for diagnostic assays are needed which will not pose a safety risk to laboratory workers. The use of synthetic peptides in serological assays is one such alternative approach. In addition, identification of immunodominant epitopic regions may have application in vaccine development if they induce protective immunity. The peptide library was used to screen for antibodies recognizing human defined linear B cell epitopic regions in survivors of CCHFV infection by means of an enzyme-linked immunosorbent assay (ELISA). Two potential epitopic regions were identified on the GC glycoprotein with reactivity in 13 – 14 of 15 patients tested. Further investigation will be required to determine whether these epitopic regions also correlate with immune protection and to identify non-contiguous B cell epitopes which are likely to play an important role in antibody induction during natural infection with CCHFV. With new foci of CCHFV infections emerging in recent years, it is important to ascertain whether genomic variation will influence applicability of vaccine candidates and diagnostic assays in distinct geographic areas. Next generation sequencing techniques were used to obtain complete genome sequences for ten southern African CCHFV isolates. This is the first application of next generation sequencing technology to CCHFV isolates and proved to be a rapid and cost effective alternative to standard Sanger sequencing which can be effectively applied to the approximately 20kb CCHFV genome. The phylogenetic results confirmed that although there is extensive variability among geographically distinct CCHFV isolates at a genomic level, conserved areas are present which could be targeted for vaccine development and diagnostic purposes. The genetic variability seen results from point mutations and segment reassortment, which was shown to occur commonly in southern African CCHFV isolates. Despite the extensive variation in primary sequence, at a protein level, the motifs involved in protein function are well conserved. Prediction software analysis confirmed the presence of conserved OTU-like cysteine protease and RNA dependent RNA polymerase (RdRp) domains in the L segment of diverse southern African CCHV isolates. The RdRp is essential for viral replication while the OTU-like protease likely plays a role in immune evasion and therefore affects viral pathogenicity. Analysis of the M segment showed conservation of the basic protein coding strategy, with two structural and three non-structural glycoproteins. However, amino acid variation was notable across all predicted proteins but particularly in the variable mucin-like domain which is thought to play a role in viral pathogenicity. This study identifies targets for further investigation of viral pathogenicity which may include in vivo studies in animal models and mutagenicity assays.
Thesis (Ph.D. (Medical Microbiology and Virology))--University of the Free State, 2014
Keywords: Hemorrhagic fever; Virus diseases; Ticks as carriers of disease